Influence of body composition assessment with bioelectrical impedance vector analysis in cancer patients undergoing surgery - Cai, Bin; Luo, Lan; Zhu, Chenping; Meng, Liping; Shen, Qing; Fu, Yafei; Wang, Mingjie; Chen, Sue (Frontiers in Oncology, 2023)
Background： Malnutrition is common in patients undergoing surgery for cancers and is a risk factor for postoperative outcomes. Body composition provides information for precise nutrition intervention in perioperative period for improving patients' postoperative outcomes.The aim was to determine changes in various parameters of body composition and nutritional status of patients during perioperative period.Methods: 92 patients diagnosed with different type of cancer who were undergoing surgery were divided into gastrointestinal cancer group and non-gastrointestinal cancer group. Assessment of body composition by bioelectrical impedance vector analysis (BIVA) in patients the day before surgery and on postoperative day 1 and 1 day before discharged and compared the changes between two groups.The nutritional status of all subjects become worse after surgery, and phase angle (PA) continued to decrease in the perioperative period. Fat-free mass (FFM), fat-free mass index (FFMI), skeletal muscle mass (SMM), extracellular water (ECW), total body water (TBW), hydration and body cell mass (BCM) rise slightly and then fall in the postoperative period in patients with gastrointestinal cancer and sustained increased in non-gastrointestinal patients, respectively (P<0.05). Postoperative body composition changes in patients with gastrointestinal cancer are related to preoperative albumin, pre-albumin, hemoglobin and C-reactive protein (P<0.05), whereas postoperative body composition changes in patients with non-gastrointestinal cancer are related to age (P<0.05).Conclusions: Significant changes of body composition both in patient with gastrointestinal cancer and non-gastrointestinal cancer during perioperative period are observed. Variation in body composition for the studied populations appeared to be related to age and preoperative serum nutrition index.